Persepsi Mahasiswa Terhadap Penerapan Teknologi Di Era Digitalisasi Pada Aplikasi AyoDonor - Adellya Marsyanda Yuliyanti; Elsa Ananda Meylanisa; Nadia Kamila Ashari (Institut Nalanda, 2024)
The Indonesian Red Cross (PMI) is facing a significant shortage of blood stocks. As a solution, the Ayodonor app was launched to increase the participation of blood donors, especially among students. The study aims to understand students' perceptions and interests in the application of Ayodonor in the era of digitalization. The method used is quantitative research with a Likert scale survey. Data was collected from 50 students through a questionnaire consisting of 15 questions. The results show that many students feel the Ayodonor application is easy to use to find information about the location of nearest blood donors, blood stocks, and routine blood donor schedules.